A study of DEF6 granule formation using biophysical and cellular methods - Mollett, Eleanor (2015)
DEF6 is a Rho-Guanine Nucleotide Exchange Factor (GEF) with a poorly characterised role in T-cell receptor signalling and unknown structure1-3. Its importance in T-cell signalling has been highlighted by observations that DEF6-deficient T cells display defective actin polymerisation and polarisation, have a decreased susceptibility to CD3-induced apoptosis4, and exhibit aberrant expression of the inflammatory cytokine IL-172. DEF6 is a GEF for Rho-family GTPases including CDC42, RhoA and Rac11, which unlike other Rho-GEFs exhibits a reversal of the N-C terminal orientation of the DH and PH domains only found in DEF6 and its homolog in B-cells, SWAP70. Through this role DEF6 has been shown to be involved in the spatiotemporal organisation of T cell signalling through the GTPase CDC425. DEF6-deficient mice have been shown to develop autoimmune diseases and have also been shown to be resistant to the development of other autoimmune diseases, indicating a loss of control of the immune response. The molecular mechanism behind these phenotypes remains to be identified. Exogenously expressed DEF6 has been shown to form cytoplasmic granules under conditions of arrested translation, similar to processing bodies and stress granules which are involved in translational regulation. Data presented here furthers this work and demonstrates endogenous DEF6 forms granules in activated T-cells. Exogenously expressed DEF6 shows partial co-localisation with markers of P-bodies, and demonstrates slow recovery from FRAP indicating a structural role within granules. The granules move within the cell, and analysis of this movement suggests the granules move via active transport, suggesting a link to the microtubule network. Examination of the individual domains of DEF6 demonstrates that the N-terminus is likely to have a role in the co-localisation of DEF6 with P-bodies, whilst the C-terminal DHL domain drives aggregation of DEF6 into granules. Data here confirms the predicted formation of a coiled-coil structure within the DHL domain.